The role of industry specialization of audit companies in detecting fraud in the financial statement - الطائي بشرى فاضل; الطائي بشرى فاضل; سلمان حسين فخري (Journal of Economics and Administrative Sciences, 2019)
Abstract: The aim of the research is to demonstrate the impact of the professional specialization of the audit companies in the detection of fraud in the financial statements of the economic units listed in the Iraqi market for securities for the period 2014-2015 through the application of the model (Carcello) to test the hypothesis of research on the impact of professional specialization of audit companies in the detection of fraud in lists The effect of the variables was revealed through the use of statistical models of logistic regression model and correlation coefficient. After testing the hypotheses of the research, a number of conclusions were reached. The most important was the existence of a significant relationship between the professional specialization of the auditing companies and the discovery of fraud in the financial statements of companies listed in the Iraqi market for securities, The research presented a set of recommendations, the most important of which is to encourage Iraqi audit firms to specialize in the profession. This is important in increasing the ability of the auditing company to identify the problems of the sector and enables it to plan well for the audit process, which increases its ability to detect the major errors and distortions in the financial statements, High level of quality, as well as the need for the Council of the profession of auditing and auditing conferences and scientific seminars and training courses and obligate auditing companies and offices to participate in the various modern audit topics to increase the expertise of the Office scientifically and work Which increases the expertise, knowledge and specialization of audit firms, which ensures better audit services to detect fraud in the financial statements and thus improve audit quality.